Determination of hand functionality in patients with rheumatoid arthritis based on the results of a physical therapy programme - A. Nogas; I. Grygus (Kazimierz Wielki University, 2022)
At present, there is a significant increase in the prevalence of rheumatoid arthritis, which significantly affects the patient's quality of life and leads to a permanent loss of their ability to work, which is an important medical and social problem in Ukraine. The purpose of the paper is to determine the functional capabilities of the hand in patients with rheumatoid arthritis according to the results of the physical therapy programme. Materials and methods. The study examined 188 patients with rheumatoid arthritis, whose average age was 44.9±7.6 years. All patients were randomly assigned to the control (n=92) and intervention (n=96) groups. Patients in the control group underwent rehabilitation in accordance with the recommendations of the regulatory document of the Ministry of Health of Ukraine. For the patients of the main group, a rehabilitation intervention technology was scientifically substantiated and developed, including physical therapy means with a personalised approach to each patient, taking into account the factors affecting the level of functional impairment and quality of life. The physical therapy programme included the following elements: therapeutic exercises, therapeutic massage, physiotherapy, hydrotherapy, orthotics, kinesiotaping of the upper extremities, mechanotherapy and psychological support. The Sollerman hand function test was used to determine the functional capabilities of the hand. Results. Increased mobility in the joints of the upper extremities and muscle strength 3 months after both standard treatment and physical therapy contributed to the improvement of manipulative function and activity of the hand in everyday life, as evidenced by the Sollerman test. However, significantly better changes occurred in patients of the main group compared to the control group. Thus, in patients of the main group, after 3 months, the average Sollerman test scores increased to 65.1±5.3 points, in the control group this figure was significantly lower than 61.8±3.6 points (±S) (р<0,05). Accordingly, the average Sollerman test score in patients of the main group increased from 65.1±5.3 points to 70.2±6.3 points, which is significantly higher than in patients of the control group - from 61.8±3.6 points to 65.1±3.8 points (±S) (р<0,05). Conclusion. After a 6-month course of physical therapy, patients in the main group showed better results in the Sollerman test than in the control group, which indicates the effectiveness of the proposed technology of rehabilitation measures. Consequently, the functional capacity of the hands significantly increased in the patients of the main group, which improved self-care, performance, daily activity and quality of life.